Evaluation of Nutrient Canals in the Anterior Region of the Mandible in Patients Referring to Radiology Department of Islamic Azad University of Isfahan by Using Cone-Beam Computed Tomograph - Maryam Torkian; Azade Torkzadeh; Shahab Etemadi (Isfahan University of Medical Sciences, 2022)
The nutrient canals in the anterior region of the mandible are derived from the incisive branch of the inferior neurovascular bundle the damage of which in any surgery could lead to more hemorrhage and postoperative paresthesia. Evaluating the incidence and anatomical location of these canals using dental CBCT is the purpose of this study.Materials & Methods:In this study, the CBCT scans of 196 patients-consist of 89 women and 107 men with a mean age of 49.1 from the archive of the radiology department of Isfahan Islamic Azad University were scrutinized. Sex, location, number, size (mesial-distal and buccal-lingual diameter), shape (round or ovoid) of nutrient canals were recorded. Results were analyzed using Mann-Whitney, Independent T-test, and Kruskal-Wallis test. (p value < 0.05).Results:There are nutrient canals in 83.6% of the cases, in most of the cases (73.4 %), two nutrient canals in the anterior region of the mandible were detected. The independent t test showed that the average mesial-distal (p value = 0.48) and buccal-lingual (p value = 0.40) nutrient foramen diameter in between dentate and edentulous ones had no meaningful relation. The number of nutrient canals in the anterior region of the mandible in dentate was statistically higher than the edentulous ones (p value < 0.001).Conclusion:There were nutrient canals present in most of the cases. There was no significant correlation between age and the number of nutrient canals in the anterior region of the mandible. There was no significant correlation between sex and the number of nutrient canals in the anterior region of the mandible. There was significant correlation between dentate and edentulous ones and the number of nutrient canals in the anterior region of the mandible. Preoperative knowledge of these findings via CBCT scans would be useful to prevent the complications of mandibular surgery